Effect of Paclobutrazol on Fiber Quality of Cotton (Gossypium hirsutum L.) - Temiz, Mefhar; Cimen, Ismail; Karahan, Ender (Asian Journal of Chemistry, 2010)
An important objective for using plant growth regulators in cotton is to balance vegetative and reproductive growth as well as to improve lint yield and fiber quality. Field study was conducted in a randomized complete block design with 4 replications under irrigated conditions in the Southeastern Anatolia Region of Turkey to determine fiber technological properties of cotton to soil applications of 0.05 and 0.1 g/m2 doses of the paclobutrazol, gibberellin biosynthesis inhibitors, were applied once after the first and second irrigation for the growing season. Compared with the untreated control, application of paclobutrazol significantly affected fiber micronaire, uniformity and short fiber content parameters, whereas there were no significant differences in fiber strength and length parameters.